1974
DOI: 10.1037/h0035910
|View full text |Cite
|
Sign up to set email alerts
|

Locus of control and learned helplessness.

Abstract: Failure to escape, the defining characteristic of learned helplessness, was investigated with perceived and instructed locus of control 5s in a learnedhelplessness paradigm. Three groups, equally divided between internals and externals and counterbalanced for sex, received different treatments with an aversive tone prior to the testing for helplessness. The first group could neither escape nor avoid an aversive tone, the second group could escape the tone, and the third group was not exposed to the treatment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
242
2
28

Year Published

1976
1976
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 542 publications
(289 citation statements)
references
References 12 publications
10
242
2
28
Order By: Relevance
“…Within the control group, this difference was even more pronounced , with internal subjects solving an average of 8.3 anagrams and external subjects solving 5.1 anagrams [t(1 7) =2.32, p < .0 1] . Such results were in keeping with the stud ies by Hiroto (1974) and Jones et al (1977), which suggested that external subjects would make fewer attempts at problem solutions than would internal subjects .…”
Section: Resultssupporting
confidence: 71%
“…Within the control group, this difference was even more pronounced , with internal subjects solving an average of 8.3 anagrams and external subjects solving 5.1 anagrams [t(1 7) =2.32, p < .0 1] . Such results were in keeping with the stud ies by Hiroto (1974) and Jones et al (1977), which suggested that external subjects would make fewer attempts at problem solutions than would internal subjects .…”
Section: Resultssupporting
confidence: 71%
“…Learned helplessness has been studied in cats (Seward & Humphrey, 1967), cockroaches (Brown, Busby, & Klopfenstein, (1992); Brown, Howe, & Jones (1990);Brown, Hughes, & Jones, 1988;Brown & Stroup, 1988;Brown, Anderson, & Scruggs, 1994), dogs (Overmier, 1968;Overmier & Seligman, 1967;Seligman & Groves, 1970;Seligman & Maier, 1967;Seligman, Maier, & Geer, 1968), gerbils (Brown & Dixon, 1983), goldfish (Nash, Martinez, Dudeck, & Davis, 1983;Padilla, Padilla, Ketterer, & Giacalone, 1970;Brown, Smith, & Peters, 1985), humans (Hiroto, 1974;Thornton & Jacobs, 1971;Hokanson, DeGood, Forrest, & Brittain, 1971;Fosco & Geer, 1971;Glass & Singer, 1972;Hiroto & Seligman, 1975;Klein, Fencil-Morse, & Seligman, 1976;4 Krantz, Glass, & Snyder, 1974;Roth, 1973;Roth & Bootzin, 1974;Roth & Kubal 1975;Thornton & Jacobs, 1971), mice (Braud, Wepman, & Russo, 1969), rats (Maier, Albin, & Testa, 1973;Seligman & Beagley, 1975;Seligman, Rosellini, & Kozak, 1975), and slugs (Brown, Davenport, & Howe, 1995;Brown, Davenport, & Howe, 1994). Even though learned helplessness is deep seated and ubiquitous behavior, interest in learned helplessness has been steadily decreasing since the 1980s.…”
Section: Chapter II Literature Reviewmentioning
confidence: 99%
“…The behavioral analogs between learned helplessness and human depression are of particular note. Hiroto (1974) investigated learned helplessness in humans utilizing a triadic design typical of animal learned helplessness research. The triadic design consisted of an escape condition group that could escape an aversive noise by a button press, an inescapable condition group yoked to the escape condition group that could not escape the noise, and a group that received no noise.…”
Section: Chapter II Literature Reviewmentioning
confidence: 99%
“…When aversive events occur despite one's efforts to prevent them, motivation to control events is reduced both in animals (Maier & Seligman, 1966) and in humans (Hiroto, 1974;Hiroto & Seligman, 1975). When control is later made possible, the motivational deficit prevents learning from occurring.…”
Section: B Planning Is Applied Hopingmentioning
confidence: 99%